Pengembangan Media Menggunakan E-Book Creator Berbantuan Aplikasi Canva pada Pembelajaran Pendidikan Pancasila di Kelas V Sekolah Dasar - Fatma, Olsa Danya; Rahmatina, Rahmatina (TSAQOFAH, 2025)
This study is motivated by the suboptimal use of digital media in learning, which is largely due to teachers' limited ability to design and utilize media effectively. The aim of this research is to develop a learning medium in the form of an E-Book Creator supported by the Canva application for the Pancasila Education subject in fifth-grade elementary school. The method used is Research and Development (R&D) with the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. Data were collected through validation questionnaires administered to subject matter, language, and media experts, as well as practicality questionnaires from teachers and students. The trial was conducted with 12 students from SDN 06 Tujuah Koto Talago, with the main subjects being 25 students from SDN 05 Tujuah Koto Talago. Data analysis used a Likert scale. The results show that the developed media achieved a very high level of validity, with scores of 97.5% for content, 95% for language, and 98% for media. The practicality test showed very practical ratings from teachers (97.5%) and students (95.2%). The effectiveness test yielded a score of 90.4%, categorized as very effective. Therefore, it can be concluded that the E-Book Creator media supported by Canva is valid, practical, and effective in supporting Pancasila Education learning for fifth-grade elementary students and serves as an innovative solution for the contextual and accessible use of digital learning media.